Lipoma of Piriform Sinus: A Case Report and Review of the Literature - Gilberto Acquaviva; Theodoros Varakliotis; Stefano Badia; Francesco Casorati; Alberto Eibenstein; Gianluca Bellocchi (Case Reports in Otolaryngology)
The lipomas of oropharynx, hypopharynx, and larynx are so rare that up to now approximately there have been 100 cases reported. The lipomas are slow-growing lesions that are capable of reaching considerable dimensions and are often detected at a late stage. The symptoms can vary both in dimension and in location, semiobstructing the aerodigestive tract or exerting compression on adjacent structure. In this case, the lesion, which originated from the piriform sinus, was removed endoscopically urgently due to obvious signs of tissue suffering caused by stretching of the pedicle as a result of displacement of the mass. The two aims of this case report are to expose an interesting and rare case study mainly for an Emergency Room Specialist and an ENT (Ear, Nose, and Throat) Specialist involved in solving the problem and to demonstrate that the choice of an endoscopic approach is useful in order to have an optimal visualization of the lesion and to perform a total eradication. The use of endoscopic devices also allows a rapid postoperative recovery, compared to external access and optimum locoregional control in the follow-up procedures to prevent possible relapses.